Cada pastor uma igreja: trânsito religioso e atomização dos evangélicos em Uberlândia-MG - Cruz, Anna Carolina Alves (2016)
The migration of people between denominations of the same religion and the emergence of several new aspects calls a lot of attention in the religious field in contemporary Brazil, and we can wonder if this fragmentation or institutional atomization by denominations is due to dissent, ruptures, flexibility of the original beliefs, simultaneous accession to various beliefs or other reasons. Therefore, the focus of this study is to investigate and analyze if the atomization of the denominations correspond to significant doctrinal differences with regard to the aspects identified by the sociological and anthropological literature. Otherwise, it is the extent to which the many and varied denominations correspond to the establishment of a set of "emerging churches" and "independent", that is, a new way to establish not only churches, but also new doctrines, which are competing with the recognized, and settling permanently in the Brazilian religious field. To achieve these objectives we take as object of analysis Evangelical churches whose denominations characterize them, in principle, as emerging and/or independent of the Evangelical aspects. The analyses are carried out from conceptual and theoretical references extracted in bibliographical research on mobility, transit and religious conversions and are continuing with the results of field research carried out in several churches located in a significant number of districts of the city of Uberlândia, Minas Gerais. In these churches, pastors and believers are agents taken to dialogue and discuss about their stories of religious life, about the reasons for their accession to the new names and about the doctrinal differences in the face of their previous beliefs.